Hidden skewness: On the difficulty of multiplicative compounding under random shocks - Ludwig Ensthaler; Olga Nottmeyer; Georg Weizsäcker; Christian Zankiewicz (Deutsches Institut für Wirtschaftsforschung (DIW), 2013)
Multiplicative growth processes that are subject to random shocks often have a skewed distribution of outcomes. In a number of incentivized laboratory experiments we show that a large majority of participants either strongly underestimate skewness or ignore it completely. Participants misperceive the outcome distribution's spread to be far too narrow-band and they estimate the median to lie too close to the distribution's center. The observed bias in expectations is irrespective to risk preferences and fairly robust to feedback. It is consistent with a behavioral model in which geometric growth is confused with linear growth. The misperception is a possible explanation of investors' difficulties with real-world financial products like leveraged ETFs.
Is replaced by the following version: http://hdl.handle.net/10419/201410
Keywords: C91; D03; D14; G02; 330; Behavioral Economics; Irrational Expectations; Binomial Tree